EVOLUTION OF THE NORTHERN ALXA BLOCK IN THE PALEOZOIC: CONSTRAINTS FROM GEOCHRONOLOGY, GEOCHEMICAL CHARACTERISTICS AND ZIRCON HF ISOTOPES OF GRANITOIDS - Lei Zhang; Tao Wang; Jian-jun Zhang; Xing-jun Shi; Tong Ying (Геодинамика и тектонофизика, 2017)
The Alxa block is situated to the south of the CAOB, situated to the east of the Tarim block and west of the NCC. Voluminous intrusive and extrusive rocks outcrop in the northern Alxa block and adjacent southern CAOB. Most of them are thought to be related to the closure of the Paleo-Asia Ocean and subsequent collision [Wu, 1993; Wu et al., 1998; Zhang et al., 2013; Dan et al., 2016].